2021
DOI: 10.1111/cpr.13078
|View full text |Cite
|
Sign up to set email alerts
|

The intact parasympathetic nerve promotes submandibular gland regeneration through ductal cell proliferation

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 36 publications
3
12
0
Order By: Relevance
“…Given that the origin of the parasympathetic preganglionic is neurons, SSN plays a key role in innervating lacrimal gland and SMG ( Mitoh et al, 2017 ). Previous studies have reported that parasympathetic denervation give rise to loss in SMG weight and decrease in AQP5 expression ( Azlina et al, 2010 ; Wang et al, 2021 ), which was also observed in our study ( Figures 4B,F ). Therefore, we speculated that hyperglycemia may not only cause SMG injury, but also induce SSN damage, both of which lead to diabetes xerostomia.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Given that the origin of the parasympathetic preganglionic is neurons, SSN plays a key role in innervating lacrimal gland and SMG ( Mitoh et al, 2017 ). Previous studies have reported that parasympathetic denervation give rise to loss in SMG weight and decrease in AQP5 expression ( Azlina et al, 2010 ; Wang et al, 2021 ), which was also observed in our study ( Figures 4B,F ). Therefore, we speculated that hyperglycemia may not only cause SMG injury, but also induce SSN damage, both of which lead to diabetes xerostomia.…”
Section: Discussionsupporting
confidence: 91%
“…It has been reported that the expression level of AQP5 in SMG is regulated by the parasympathetic nerve ( Hosoi et al, 2020 ). Parasympathetic nerves are closely associated with SGs regeneration, and intact parasympathetic innervation facilitates SMGs regeneration ( Wang et al, 2021 ). Given that the origin of the parasympathetic preganglionic is neurons, SSN plays a key role in innervating lacrimal gland and SMG ( Mitoh et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The immunohistochemical assay was performed as previously described [ 27 ]. The primary antibodies against VEGFA, CD31, and PCNA were used.…”
Section: Methodsmentioning
confidence: 99%
“…Under anesthesia, the unilateral parotid excretory duct was ligated, according to a previously reported procedure [18]. Salivary glands recover when the ligation is released 7 days after the duct ligation [19,20]. We previously reported that parotid gland morphology showed weak atrophy of acinar cells in some samples on day 3 of duct ligation, whereas most acinar cells in the parotid gland were atrophied on day 7 of duct ligation [18].…”
Section: Ductmentioning
confidence: 99%